Using the InterSCSimulator to Evaluate Systems and Urban Scenarios - Santana, Eduardo Felipe Zambom; Kon, Fabio Kon (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2020)
The InterSCSimulator is a scalable, open-source Smart City simulator. The primary use of this tool is to evaluate complex Smart City scenarios and to test Smart City systems such as software platforms and applications. This simulator was already used in different contexts, such as to generate workload to Smart City platforms experiments, to evaluate the impacts of autonomous vehicles systems, and to assess the impact of a new subway line in São Paulo. This paper presents the main features and use cases of the InterSCSimulator, providing an information source to possible new users and contributors to this project.